CHARACTER EDUCATION METHODS AT ISLAMIC BOARDING SCHOOL - Qudsi Mutawakil Husaini; Aan Hasanah; Bambang Samsul Arifin (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2024)
This article discusses the method of character education in Islamic boarding schools. This research is a library research, documentary data collection method, while the analysis uses content analysis. The results showed that character education in boarding schools proved to be more effective than in schools or madrassas, because boarding schools are able to develop students from various aspects, both in terms of intellectual, emotional and religious character building, so that the output of boarding schools is born with knowledge and morals or character. The success in shaping the character of boarding students is due to boarding students in boarding schools under the guidance and supervision of the boarding school kyai, the exemplary role model of the boarding school kyai and his authority as a religious leader at school and the learning atmosphere at school. In addition, the boarding school education process emphasises aqidah, worship and akhlak karimah with methods: exemplary, habituation, giving advice, motivation, persuasion, and stories.